Peran Stewarding Terhadap Efisiensi Kerja Food And Beverage Product Departement, Hotel Burza Yogyakarta - Dwi Endaryanti; Ade Riawan (Journal of Tourism and Economic, 2025)
Stewarding plays a significant role in supporting the work efficiency of the Food and Beverage Product Department in a hotel. This study aims to analyze the role of stewarding in enhancing work efficiency at Burza Hotel Yogyakarta using a qualitative approach. Data were collected through interviews with the Food and Beverage Manager, Executive Chef, stewarding staff, and kitchen staff, while non-participant observation was conducted on all kitchen operational activities. The findings reveal that the role of stewarding goes beyond cleanliness and sanitation, encompassing the management of kitchen equipment inventory to ensure smooth operations. Therefore, stewarding plays a crucial role in improving the work efficiency of the Food and Beverage Department at Burza Hotel Yogyakarta. This study emphasizes that optimizing the function of stewarding is a vital element in supporting the sustainable operations of the Food and Beverage Department. It is expected that the findings of this research can serve as a reference for other hotels in optimizing the role of stewarding to improve work efficiency in the Food and Beverage Department.